An apparatus to apply granular insecticides adapted to an animal-drawn planter - Finch, E. O.; Cruz, I.; Ramalho, M. A.P. (Pesquisa Agropecuaria Brasileira, 2014)
This paper presents an attachment for an animal-drawn planter which applies granular insecticides jointly with the planting operation. Addition of the device to the planter (which can plant corn and dry beans individually or interplant the two crops in the same furrow as well as apply starting fertilizer) permits excellent control of early pests of both crops.